Efficacy and Safety of a Stimulator Using Low-Intensity Pulsed Ultrasound Combined with Transcutaneous Electrical Nerve Stimulation in Patients with Painful Knee Osteoarthritis - Eu-Deum Kim; Yu Hui Won; Sung-Hee Park; Jeon-Hwan Seo; Da-Sol Kim; Myoung-Hwan Ko; Gi-Wook Kim (Pain Research and Management)
Objective. Studies regarding the combination of ultrasound and transcutaneous electrical nerve stimulation (TENS) are rarely reported. In this study, we aimed to elucidate the efficacy and safety of a stimulator using low-intensity pulsed ultrasound (LIPUS) combined with TENS in patients with painful knee osteoarthritis (OA). We evaluated the effectiveness of this therapy against pain, physical function, and cartilage regeneration. Moreover, we aim to prove the superiority of the effects of LIPUS combined with TENS therapy compared with only TENS therapy. Methods. Of the 40 included patients, aged 45–85 years with painful knee OA, 20 patients received only TENS therapy and 20 patients received LIPUS combined with TENS therapy for 8 weeks (a total of more than 80 treatment sessions). We evaluated visual analogue scale (VAS), Western Ontario and McMaster Universities (WOMAC) osteoarthritis index, MOS 36-Item Short-Form Health Survey (SF-36), and femoral articular cartilage (FAC) thickness. The evaluation was performed at three visits: visit 1 (V1, pretreatment, within 28 days after screening), visit 2 (V2, posttreatment period 1, ±3 days after treatment), and visit 3 (V3, posttreatment period 2, 21 ± 3 days after treatment). Results. We expected that LIPUS combined with TENS therapy would be superior to only TENS therapy. However, there was no significant difference between the two therapies. In the within-group comparison, both treatments (only TENS therapy and LIPUS with TENS therapy) demonstrated statistical differences from baseline values for pain and physical function outcomes. FAC thickness showed no significant differences after treatment in both groups. Conclusion. The effects of a stimulator using LIPUS with TENS on pain relief and functional improvement were not superior to the only TENS therapy. Cartilage regeneration, which was expected as an additional benefit of LIPUS, was also not significantly evident. Therefore, further investigation is warranted to determine whether the combination therapy is beneficial. This trial is registered with KCT0003883.